Accessibility of Digital Financial Services in East Nusa Tenggara Province - Langoday, Thomas Ola (Jurnal Manajemen Pelayanan Publik, 2024)
The purpose of this study is to explore and analyze the accessibility readiness of digital financial services of each district in East Nusa Tenggara province, Indonesia. This research was conducted using the content analysis method. The data used is secondary data derived from various sources, especially Bank Indonesia and the Financial Services Authority. The research sample was district governments in East Nusa Tenggara province, totaling eight districts. Data analysis was also conducted on information from communication network providers regarding the infrastructure of internet availability and telecommunication services in each district to support the success of digitization-based public services. The result is that all regions have good internet access and telecommunication providers by cooperating with the government and telecommunication service providers so that the digital financial service system can be implemented properly. Of course, the next step requires a combination of technology and human approaches to strengthen the enabling mechanism and evaluation of financial inclusion.